Milking an opportunity in Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Locally produced fresh camel milk and sweetened yoghurt are now on sale in Timbuctu, Mali. A group of Touareg families have formed the Salamett Albadan association and run a herd of camels exclusively dedicated to milk production. The project...